The efficacy of prison farms towards food security at Chikurubi Maximum Prison - Panganai, Munyaradzi Persuade (Midlands State University, 2017)
The research sought to find out the contribution of Chikurubi Farm Prison Towards Food Security in the ZPCS. The ZPCS has been affected by food insecurity and due to several factors that include the nation’s economic problems and successive droughts. The concept of food insecurity caused immense suffering to inmates. This has caused the student to research how Chikurubi Farm Prison can contribute to food security in the ZPCS. This research sought to explain the food security situation in the ZPCS. Causes of food security and insecurity were also highlighted. A detailed explanation and analysis of the production systems in the ZPCS was made with potential production systems being highlighted. Factors that affect production were listed and explained. The challenges that are faced by the ZPCS as far as food security is concerned were explained with a view of finding a way forward for prisons to successfully tackle the issue of food insecurity in future.